2020
DOI: 10.1002/hep.31008
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Therapy With ARC‐520 Results in Prolonged Hepatitis B Surface Antigen Response in Patients With Chronic Hepatitis B Infection

Abstract: Background and Aims ARC‐520, the first an RNA interference (RNAi) therapeutic, was designed to reduce all RNA transcripts derived from covalently closed circular DNA, leading to a reduction in viral antigens and hepatitis B virus (HBV) DNA. Approach and Results We aimed to evaluate the depth of hepatitis B surface antigen (HBsAg) decline in response to multiple doses of ARC‐520 compared to placebo (PBO) in two randomized, multicenter studies in nucleoside/nucleotide ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 19 publications
0
87
0
1
Order By: Relevance
“…Instead of currently available NUCs, which are poorly effective in diminishing HBV antigen concentrations, new and more efficient antivirals should be employed in the future, once clinically available, to reduce more rapidly and more efficiently the antigen load and the number of infected hepatocytes. They include RNA interference (RNAi) molecules, which can directly target HBV mRNAs, allowing reduction in HBsAg serum titers (177), HBV capsid assembly inhibitors and nucleic acid polymers (NAPs), as HBsAg release inhibitors (178)(179)(180). Since decline of antigen alone is expected to be insufficient, additional mechanisms should be targeted to further improve T cell responsiveness.…”
Section: Perspectives For Novel Therapeutic Strategiesmentioning
confidence: 99%
“…Instead of currently available NUCs, which are poorly effective in diminishing HBV antigen concentrations, new and more efficient antivirals should be employed in the future, once clinically available, to reduce more rapidly and more efficiently the antigen load and the number of infected hepatocytes. They include RNA interference (RNAi) molecules, which can directly target HBV mRNAs, allowing reduction in HBsAg serum titers (177), HBV capsid assembly inhibitors and nucleic acid polymers (NAPs), as HBsAg release inhibitors (178)(179)(180). Since decline of antigen alone is expected to be insufficient, additional mechanisms should be targeted to further improve T cell responsiveness.…”
Section: Perspectives For Novel Therapeutic Strategiesmentioning
confidence: 99%
“…In a phase II trial, weekly doses of 2 mg/kg produced only moderate HBsAg reductions, possibly due to the expression of HBsAg from integrated HBV-DNA, indicating the need for RNAi therapeutics that target viral transcripts regardless of origin, either as episomic cccDNA or integrated chromosomically. 18 More recent data have shown that another RNAi named ARC-530 produces a significant and sustained decline in serum HBsAg. 18 ARO-HBV (JNJ-3989) contains two RNAi that silence all mRNA produced from HBV cccDNA and host integrated viral DNA ( Figure 1).…”
Section: Hbv Translator Inhibitorsmentioning
confidence: 99%
“…This observation was further investigated in chimpanzees and attributed to notable HBsAg expression from integrated copies of the HBV genome, many of which lacked the ARC-520 target site, which was commonly deleted upon integration. In subsequent phase II trials (NCT02604199, NCT02604212), ARC-520 reduced HBsAg expression for at least 85 days in both HBeAg-negative and HBeAg-positive nucleoside/nucleotide analogue-experienced patients [102]. However, the data showed that absolute reductions in HBsAg were moderate, again likely a result of HBsAg expression from integrated HBV DNA.…”
Section: Clinical Trials Evaluating Rnai-based Treatment For Hbv Infementioning
confidence: 98%
“…Use of siRNAs has reached clinical evaluation for numerous diseases, including chronic HBV infection. GalNAc-conjugated siRNAs developed in preclinical studies by Arrowhead Pharmaceuticals [96,97] have been tested in clinical trials for HBV treatment [102] (Table 1). The ARC-520 siRNA was found to be well-tolerated with no serious adverse events in healthy volunteers (NCT01872065, clinicaltrials.gov) [96].…”
Section: Clinical Trials Evaluating Rnai-based Treatment For Hbv Infementioning
confidence: 99%